2013
DOI: 10.1007/s10461-013-0574-1
|View full text |Cite
|
Sign up to set email alerts
|

Unmet HIV Service Needs Among Black Men Who Have Sex with Men in the United States

Abstract: The National HIV/AIDS Strategy (NHAS) clearly emphasized the need to provide services to black men who have sex with men (MSM). However, there are no estimates of the unmet HIV-related service delivery needs among black MSM. We estimate that of 195,313 black MSM living with HIV in the US, 50,196 were not yet diagnosed, and 145,118 were aware of their seropositivity (of whom 67,625 were not linked to care and 77,493 were linked to care). Also, of those already diagnosed, ~43,390 had undetectable viral load and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Although historically much of the HIV prevention and treatment efforts in the US have been carried out by community-based HIV/ AIDS organizations, many of these agencies are likely unequipped within their currently existing infrastructure to not only raise awareness of PrEP, but seek out, engage, and provide ongoing care for individuals who are on PrEP or candidates for PrEP. This scenario leaves open the need to either enhance and improve services provided by HIV/AIDS medical providers, [44][45][46] or to train primary care providers in sexual health assessments and CDC guidelines on PrEP use, and invigorate efforts to promote PrEP. Further, our study focused primarily on challenges relating to awareness of PrEP.…”
Section: Prep Awareness Among Bmsm 427mentioning
confidence: 99%
“…Although historically much of the HIV prevention and treatment efforts in the US have been carried out by community-based HIV/ AIDS organizations, many of these agencies are likely unequipped within their currently existing infrastructure to not only raise awareness of PrEP, but seek out, engage, and provide ongoing care for individuals who are on PrEP or candidates for PrEP. This scenario leaves open the need to either enhance and improve services provided by HIV/AIDS medical providers, [44][45][46] or to train primary care providers in sexual health assessments and CDC guidelines on PrEP use, and invigorate efforts to promote PrEP. Further, our study focused primarily on challenges relating to awareness of PrEP.…”
Section: Prep Awareness Among Bmsm 427mentioning
confidence: 99%
“…The use of biomedical technologies in preventing the spread of HIV will fail if those in need are not connected to care that can facilitate access to and monitor the use of these technologies. (5, 6) Within the current HIV prevention and treatment health care landscape, it is well understood that those who are without successful engagement in care suffer worse morbidities and greater mortality than those in care and that rates of engagement in care are limited for many at elevated risk for disease. (7) Even brief lapses in care increase morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that HIV‐positive black MSM are more likely to be unaware of their infection compared to white MSM , and less likely to initiate treatment for HIV and achieve HIV viral suppression (VS) , which dramatically reduces HIV transmissibility . Black MSM are more likely than other racial and ethnic groups to report sexual partnerships with other black men; given the existing high prevalence of untreated HIV infection among black MSM, they are thus more likely than other racial and ethnic groups to be exposed to HIV through sex . Identifying black MSM and TGW with undiagnosed HIV infection and initiating treatment for them is essential to good health outcomes ; it is also a central focus of the US strategy to control HIV and eliminate the persistent HIV disparities impacting black MSM and TGW in the US .…”
Section: Introductionmentioning
confidence: 99%